Having Children with Mental Retardation - Sri Endriyani; Yunike Yunike (International Journal of Public Health Science (IJPHS), 2017)
Mental Retardation is a condition in which the intelegency function is under average, which began during the developmental period. Children with mentally retarded have limited mental function, communication skills, ability to maintain themselves and social skills. These conditions impact the mothes’s they responsible to train children’s ability to be independent. The purpose of this study is to explore the mothers’ experience having children with mental retardation at Special School for mentally retarded (SLB) of Karya Ibu Palembang, Indonesia. This is a qualitative research with fenomenology approach from five partisipants with indept interview. Five themes were get including can’t accept reality, burden, the social stigma,need support from relatives, worry about the future, and admitting God’s will. The Adaptation behaviors found in this study are the acceptance of children’s condition, and loving the children thoroughly.